Asymmetric inverse-electron-demand 1, 3-dipolar cycloadditions of cyclopentadienones and thiophene-1, 1-dioxide with C, N-cyclic azomethine imines. Issue 36 (13th April 2022) - Chen, Chen; Yang, Xing-Xing; Zhao, Zhi; Han, Bo; Du, Wei; Chen, Ying-Chun
Abstract : A Pd(0)-catalysed and ligand-controlled diastereodivergent inverse-electron-demand 1, 3-dipolar cycloaddition reaction of carbonates of 4-hydroxy-2-cyclopentenones and C, N -cyclic azomethine imines was presented. Abstract : The normal 1, 3-dipolar cycloaddition between the carbonates of 4-hydroxy-2-cyclopentenones and C, N -cyclic azomethine imines can be switched to an inverse-electron-demand version under Pd(0) catalysis, by in situ generation of HOMO-raised η 2 -Pd(0)-cyclopentadienone complexes. An array of fused heterocyclic architectures are constructed with high levels of diastereo and enantioselectivity, and diastereodivergent synthesis is well realised by tuning the bifunctional phosphine ligands. In addition, similar reaction with in situ formed thiophene-1, 1-dioxide is compatible by using a chiral bisphosphine ligand, and the fused cyclic sulfone frameworks are afforded with high stereoselectivity.